PHENOMENOLOGY OF GUILT: SOME REMARKS ON JASPERS’ AND HEGEL’S NOTION OF GUILT - Todorović, Tanja D. (Glasnik Advokatske komore Vojvodine, 2020)
Jaspers inquires into the problem of guilt in closer relation with the idea of communication, which finds its metaphysical foundation in the unspecified idea of humanity. His distinction between the four types of guilt can find its foundation in metaphysical guilt. In his philosophical conception, Jaspers manages to adopt certain insights of Kant’s ethics, in this context we shall emphasize the connection between moral and metaphysical guilt. In the framework of Hegel’s critique of Kant we shall explicate how the four types of guilt that Jaspers distinguishes (moral, metaphysical, criminal, and political) can be reduced to moral and legal guilt.